THE FUTURE OF VETERINARY MEDICINE: CUTTING-EDGE TECHNOLOGIES AND THERAPIES - Urfeya, Mirza; Farooq , Uiase Bin (International Journal of Allied Sciences (IJAS), 2022)
As technology continues to advance, the field of veterinary medicine is experiencing a paradigm shift, with numerous groundbreaking innovations and therapies emerging. This article delves into an in-depth discussion of these developments, emphasizing advancements in areas such as stem cell therapy, fiber optic technology, anesthesia and anesthetic monitoring, and laser surgery. The clinical application of stem cells in veterinary medicine is still in its nascent stages, but it is already redefining the concept of healing in various animal species. The incorporation of fiber optic technology in diagnostics has been one of the most thrilling advancements in the field. Moreover, Alfaxalone, the latest anesthetic induction agent approved by the FDA, and surgical lasers have noticeably improved operating room experiences. This review provides a concise overview of these essential innovations, as well as other emerging therapies that are consistently enhancing the health and longevity of animals